Use of Quranotherapy in children with cancer: A type of traditional and complementary medicine: Uso de la coranoterapia en niños con cáncer: Un tipo de medicina tradicional y complementaria - Caksen, Huseyin (2025)
Traditional and complementary medicine (T&CM) use is common in both in adult and pediatric oncology worldwide. Quranotherapy, a type of T&CM, is also widely used by cancer patients and their parents/caregivers. A limited number of studies have shown that Quranotherapy is beneficial in improving adjustment and in reducing pain and anxiety in children with cancer.